Insulin regimens for newly diagnosed children with type 1 diabetes mellitus in Australia and New Zealand: A survey of current practice. (20th July 2017) - Selvakumar, Dharrshinee; Al‐Sallami, Hesham S; de Bock, Martin; Ambler, Geoffrey R; Benitez‐Aguirre, Paul; Wiltshire, Esko; Tham, Elaine; Simm, Peter; Conwell, Louise S; Carter, Phillipa J; Albert, Benjamin B; Willis, Jinny; et al.
Abstract : Aim: There is no consensus on the optimal insulin treatment for children newly diagnosed with type 1 diabetes mellitus (T1DM). The aims of this study were (i) to describe the insulin regimens used at diagnosis by patient age and geographical region and (ii) to explore differences between and within Australia (AU) and New Zealand (NZ) with regards to other aspects of patient management and education. Methods: An online survey of medical professionals caring for children with T1DM in AU and NZ was undertaken. Questions included clinic demographics, insulin regimen/dosing choices and patient education. Results: Of 110 clinicians identified, 100 responded (91%). The majority of those in AU (69%, P  < 0.0001) favour multiple daily injections (MDI) for all ages. In NZ, for patients < 10 years old, (twice daily (BD)) BD therapy was favoured (75%, P  < 0.0001), with MDI dominant for ages ≥ 10 years (82%, P  < 0.0001). Insulin pump therapy was never considered at diagnosis in NZ, but 38% of clinicians in AU considered using pumps at diagnosis in patients <2 years, but rarely in patients aged 2 and over (16%). Differences in clinician choices were also seen in relation to starting insulin dose. Conclusion: This is the first study to examine current clinical practice with regards to children newly diagnosed with T1DM. Practice varies across Australasia by clinician and region. This lack of consensus is likely driven by ongoing debates in the current paediatric diabetes evidence base as well as by differences in clinician/centre preference, variations in resourcing and their interpretations of the influence of various patient factors.